1996
DOI: 10.1021/jp960589h
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt Clusters in NaY Zeolite Cages:  Synthesis and Characterization

Abstract: The adsorption of Co 2 (CO) 8 onto dehydrated NaY powder under a N 2 atmosphere and into a tetrahydrofuran slurry of NaY under a CO/H 2 atmosphere predominately yielded supported Co 4 (CO) 12 and supported Co 6 -(CO) 16 , respectively. The molecular cobalt-carbonyl clusters and their decarbonylated products have been structurally characterized by in situ infrared, extended X-ray absorption fine structure (EXAFS), and diffuse reflectance spectroscopies and NO chemisorption. The infrared spectrum of the species … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
1

Year Published

1998
1998
2019
2019

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 45 publications
(80 reference statements)
2
25
1
Order By: Relevance
“…Among them, the heterogeneous catalysts prepared by metallic carbonyl cluster precursors loaded on solid supports exhibited distinct characteristics and activities in heterogeneous catalyst system [5,6]. The published studies indicated that the carbonyl precursors, such as Co 2 (CO) 8 , Co 4 (CO) 12 and Os 3 (CO) 12 [7][8][9], are excellent precursors due to their small metallic particles, which possibly emerge from the bonds between metal atoms in their zero oxidation state in these complexes. Moreover, these complexes were assumed to mimic small metallic particles covered with CO ligands [10].…”
Section: Introductionmentioning
confidence: 99%
“…Among them, the heterogeneous catalysts prepared by metallic carbonyl cluster precursors loaded on solid supports exhibited distinct characteristics and activities in heterogeneous catalyst system [5,6]. The published studies indicated that the carbonyl precursors, such as Co 2 (CO) 8 , Co 4 (CO) 12 and Os 3 (CO) 12 [7][8][9], are excellent precursors due to their small metallic particles, which possibly emerge from the bonds between metal atoms in their zero oxidation state in these complexes. Moreover, these complexes were assumed to mimic small metallic particles covered with CO ligands [10].…”
Section: Introductionmentioning
confidence: 99%
“…Many ways are used to prepare the transition metal containing zeolites: (1) by ion exchange, either from aqueous solution [2][3][4][5] or by solid-state reaction [8], (2) by hydrothermal synthesis [9], and (3) by adsorption and decomposition of volatile organometallic compounds [10].…”
Section: Introductionmentioning
confidence: 99%
“…The traditional precursor for a supported CoMo HDS catalyst is cobalt nitrate. 2a-c Recently, however, Okamoto et al2d have obtained promising results with use of Co 2 (CO) 8 as precursor. Many studies by IR spectroscopy have been made of the interactions between Co 2 (CO) 8 and Co 4 (CO) 12 and oxidic supports. Silica is the simplest of these supports. Since “Co 2 (CO) 8 (ads)” and Co 4 (CO) 12 (ads) on silica give similar IR spectra, it has been suggested that dicobalt dimerizes to tetracobalt species. , The surface of alumina is much more heterogeneous than silica, and the surface reactions are different; various surface species, including Co 2 (CO) 8 , Co 4 (CO) 12 , Co 6 (CO) 16 - x , and Co(CO) 4 - and also some unidentified α and β species, have been observed by IR spectroscopy. Similar surface species have been found on magnesia, , which is more basic than alumina, and also on zeolites, although the species formed on zeolites depend on the type of zeolite and the exchanged cation. The identification of these surface species is not always unambiguous although clear identifications are essential if we are to understand reaction mechanisms.…”
Section: Introductionmentioning
confidence: 99%